RELOCATION FOR FOOD TRADERS IN THE ICE RIVER BETWEEN FLOOD EAST CANAL CITY OF SEMARANG BASED ON SEMARANG CITY PERDA NUMBER 14 YEAR 2011 - Wardani, Diah Ayu mulya; Mulyani, Tri; Muryati, Dewi Tuti (Fakultas Hukum, Universitas Semarang, 2022)
The relocation of street vendors needs to be done as an effort to organize in order to create an order. So, in this study, we tried to examine the relocation of street vendors in the Kali Es Riverbank, East Flood Canal, Semarang City based on the Perda of Semarang City Number 14 of 2011, Constraints in relocating for street vendors in Kali Es Riverbank of the East Flood Canal in Semarang City based on the Perda of Semarang City. Number 14 of 2011 and efforts to overcome it. The research methods used include: types of juridical research, sociological, descriptive analysis specifications. The data used is primary data and is supported by secondary data, with qualitative data analysis. The results showed that: Basically, the relocation concept was implemented because in the Kali Es area, along the East Flood Canal River, floods often occur. The relocation of street vendors in the Kali Es area along the East Flood Canal River, Semarang City through 3 procedures, 1) data collection, 2) socialization and 3) providing legal certainty. With the relocation of the street vendors, it aims to overcome the flooding in the city of Semarang. Efforts made by the government in relocating street vendors such as providing a new place for them to sell. The obstacles that arise in the Guidance and Arrangement of Street Vendors (PKL) in the Kali Es area, along the East Flood Canal River, Semarang City, are: First, the low legal awareness of street vendors. Second, Weak Supervision by Semarang City Officials. Third, the relocation of places selling street vendors that are not strategic and adequate. Fourth, the economic factors of street vendors. Meanwhile, the efforts made to overcome the obstacles that arise in the Guidance and Implementation of PKL Arrangement in the Kali Es River Basin, East Flood Canal, Semarang City are: First, Provide counseling and guidance to street vendors and provide circulars and warnings both verbally and in writing to comply. existing and current legal provisions. Second, Improving supervision by conducting regular controls throughout the city of Semarang (justice operation). Third, seek new locations or land for street vendors who have not yet found a place of business. Fourth, provide training and capital assistance for street vendors.